2011
DOI: 10.1080/10810730.2011.604384
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstanding and Potential Unintended Misuse of Acetaminophen Among Adolescents and Young Adults

Abstract: Purpose Acetaminophen is highly accessible yet potentially dangerous when used incorrectly. In attempts to address concerns about acetaminophen, The U.S. Food and Drug Administration (FDA) has identified gaps in evidence about unintentional misuse among adolescents. Therefore, our objectives were to assess: adolescents’: 1) health literacy; 2) knowledge about acetaminophen; 3) recent use of over-the-counter (OTC) medicines; 4) and use of medication dosing instructions to understand the medicine and how to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 19 publications
0
43
2
Order By: Relevance
“…Given that our multiple measurements imply that health literacy skills are low for many adolescents, it is important to advance the field. There have been a few adolescent health literacy studies to date exploring the relationship between health literacy and health behaviors or outcomes, 10,13,15,20,21,23 and further research is needed to evaluate how health literacy impacts youth. Inclusion of the HAS-A on youth surveys will allow for more comprehensive data to be collected, and can also be used for the evaluation of interventions to enhance health literacy skills for adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that our multiple measurements imply that health literacy skills are low for many adolescents, it is important to advance the field. There have been a few adolescent health literacy studies to date exploring the relationship between health literacy and health behaviors or outcomes, 10,13,15,20,21,23 and further research is needed to evaluate how health literacy impacts youth. Inclusion of the HAS-A on youth surveys will allow for more comprehensive data to be collected, and can also be used for the evaluation of interventions to enhance health literacy skills for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…10 Health literacy tools used with adolescents include the Rapid Estimate of Adolescent Literacy in Medicine (REALM-Teen), 1113 the Test of Functional Health Literacy in Adults (TOFHLA), 1421 and the Newest Vital Sign (NVS). 2226 However, these instruments assess very specific skills that are one part of health literacy, such as reading ability, reading comprehension, and numeracy.…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate information given to patients about use of these drugs may cause serious results (i.e. increase in adverse reaction risk and drug interactions) (22)(23)(24).…”
Section: (178)mentioning
confidence: 99%
“…It has been shown that patients, especially those with low health literacy or low socio-economic status, may have difficulty understanding drug warning information [4], [5]. It has been argued that the language used in drug warning labels is at a reading level beyond that of the general public [6].…”
Section: Introductionmentioning
confidence: 99%